A Female With Synchronous Multiple Primary Malignant Tumors in the Esophagogastric Junction, Duodenum and Pancreas: Case Report and Review of the Literature - Du, Yongxing; Duan, Yunjie; Zhang, Lipeng; Gu, Zongting; Zheng, Xiaohao; Li, Zongze; Wang, Chengfeng (Frontiers in Oncology, 2022)
The incidence of multiple primary carcinomas (MPCs), which are defined as two or more malignancies detected in an individual person, is gradually increasing around the world. According to the timing of diagnosis for each constituent tumor, MPCs are classified into 2 categories: synchronous MPCs if constituent tumors emerge simultaneously or within 6 months or metachronous MPCs otherwise. In this report, we describe our recent observation and treatment of a female patient with synchronous primary esophagogastric junction adenocarcinoma, duodenal adenocarcinoma and pancreatic ductal adenocarcinoma (PDAC). To the best of our knowledge, this combination has not yet been reported in the literature. A crucial aspect is the decision regarding which tumor to treat initially and how to schedule further treatments according to individual tumor hazards. Our multidisciplinary team devised an individualized treatment regimen for this patient. The patient ultimately achieved an overall survival time of 18 months, which was much longer than the median survival time (6~11 months) of patients with locally advanced pancreatic cancer. Moreover, treating this rare combination raised a series of diagnostic, etiological and therapeutic questions, motivating us to carry out a critical review of the literature. In summary, an individualized treatment strategy with input from a dedicated multidisciplinary team and consideration of all options at different points along the disease trajectory is essential to optimize outcomes for patients with MPC.